Persepsi penghuni terhadap harta tanah kondominium : kajian kes : Mont' Kiara, Kuala Lumpur - Ng, Boon Chye (2004)
Residential housing is one ofbasic needs for every human being. Housing industry in Malaysia has grown tremendously due to the increased demand for housing. Land shortage problem in urban area and high land cost have influenced development ofhigh rise residential housing properties as an alternative for housing.The success of condominium development, which has been introduced since 70s, led to a tremendous growth ofcondominium developments during 80s and 90s. It also causes major changes in lifestyles from conventional housing to condominium housing. There are still demands for this unique property despite its expensive selling price. Why are there still huge demands for condominium properties? Therefore, the main objective ofthe study is to identify the resident's characteristic ofthis upmarket property in the study area. Factors that influence purchases of condominium were also studied. Besides, study on preferences on facilities and amenities were also carried out. Data sources are from distribution of questionnaires and were analyzed qualitatively. Result ofthe analysis shows that location is the main factor that affects resident's decision.Besides,the study shows that the most preference for facilities and amenities by residents is 24 hours security. It is hoped that this study could be used for guidance and reference to would be condominium developer and prospect condominium buyers.